Correction: Characteristics of Memory B Cells Elicited by a Highly Efficacious HPV Vaccine in Subjects with No Pre-existing Immunity (PLoS pathogens, 2014)
PLoS Pathog 10(10): e1004461 doi:10.1371/journal.ppat.1004461. * View Article * PubMed/NCBI * Google Scholar Citation: The PLOS Pathogens Staff (2014) Correction: Characteristics of Memory B Cells Elicited by a Highly Efficacious HPV Vaccine in Subjects with No Pre-existing Immunity.